Adverse drug events associated with vitamin K antagonists: factors of therapeutic imbalance - El-Helou, Nancy (Dove Medical Press, 2013)
BACKGROUND: Adverse drug events (ADE) occur frequently during treatment with vitamin K antagonists (AVK) and contribute to increase hemorrhagic risks. METHODS: A retrospective study was conducted over a period of 2 years. Patients treated with AVK and admitted to the emergency room of a tertiary care hospital in Beirut were included. The aim of the study was to identify ADE characterized by a high international normalized ratio (INR) and to determine the predictive factors responsible for these events. Statistical analysis was performed with the SPSS statistical package. RESULTS: We included 148 patients. Sixty-seven patients (47.3%) with an INR above the therapeutic range were identified as cases. The control group consisted of 81 patients (54.7%) with an INR within the therapeutic range. Hemorrhagic complications were observed in 53.7% of cases versus 6.2% of controls (P < 0.0001). No significant difference was noticed between cases and controls regarding the indication and the dose of AVK. Patients aged over 75 years were more likely to present an INR above the therapeutic range (58.2%, P = 0.049). Recent infection was present in 40.3% of cases versus 6.2% of controls (P < 0.0001) and hypoalbuminemia in 37.3% of cases versus 6.1% of controls (P < 0.0001). Treatment with antibiotics, amiodarone, and anti-inflammatory drugs were also factors of imbalance (P < 0.0001). CONCLUSION: Many factors may be associated with ADE related to AVK. Monitoring of INR and its stabilization in the therapeutic range are important for preventing these events.